Vitamin D and Calcimimetics in Cardiovascular Disease - Lim, Kenneth (Semin Nephrol, 2018)
Cardiovascular disease has earned its place as one of the leading non-communicable diseases that has become a modern-day global epidemic. The rising incidence and prevalence of Chronic Kidney Disease (CKD) has added to this enormous burden, given that CKD is now recognized as an established risk factor for accelerated cardiovascular disease. In fact, cardiovascular disease remains the leading cause of death in the CKD population with significant prognostic implications. Alterations in vitamin D levels as renal function declines has been invariably linked to the development of cardiovascular disease beyond a mere epiphenomenon, and has become an important focus in recent years in our search for new therapies. Another compound, cinacalcet that belongs to the calcimimetic class of agents has also taken center stage over the past few years as a potential cardiovasculo-protective agent. However, given limited well-designed randomized trials to inform us, our clinical practice for the management of cardiovascular disease in CKD has not been refined adequately. This article considers the biological mechanisms, regulation and current experimental, clinical and trial data available to help guide the therapeutic use of vitamin D and calcimmetics in the setting of CKD and cardiovascular disease.